Partial expression of Papillon-Lefèvre Syndrome - Kothiwale Shaila; Mathur Setu (Indian Journal of Dental Research, 2008)
Papillon-Lefθvre Syndrome (PLS) is a rare autosomal recessive trait, which is transmitted with an estimated frequency of one to four per million individuals. It is characterized by palmar plantar keratosis and severe early-onset periodontitis affecting both deciduous and permanent dentition. In this report, we present clinical, microbiological and leukocyte function test findings of a thirty-five year-old patient with symptoms typical of Papillon-Lefθvre Syndrome except for premature loss of deciduous and permanent dentition. The patient exhibited palmar plantar keratosis and an isolated, moderately deep periodontal pocket in the third quadrant. No anaerobic bacteria were isolated from the plaque culture. The neutrophil function test revealed defective chemotaxis and phagocytosis while intracellular killing and respiratory burst were normal.